2010
DOI: 10.1002/agr.20261
|View full text |Cite
|
Sign up to set email alerts
|

Constraints and determinants of compliance with EurepGap standards: a case of smallholder french bean exporters in Kirinyaga district, Kenya

Abstract: The authors identify constraints and critical factors that influence compliance with EurepGap standards among French bean smallholder exporters in Kirinyaga District, Kenya. A probit model was used to determine the factors influencing the EurepGap compliance decision while descriptive statistics were used to identify the major constraints to compliance. Results indicate that the high initial cost of compliance is a major constraint on compliance. This arises from the need to purchase recommended agro-chemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 6 publications
(3 reference statements)
11
54
1
7
Order By: Relevance
“…Previous studies investigating the factors of the internal business environment that have an impact on farmers' certification-related decisions also identified some market and public policy factors (Karipidis et al 2009;Asfaw et al 2010a, b;Masakure et al 2011;Muriithi et al 2011;Kersting and Wollni 2012;Karipidis and Tselempis 2014;Soltani et al 2014;Veldstra et al 2014). We select thirteen factors of the external business environment identified in these studies and we also add three factors that we identified in some in-depth interviews with producers as crucial in order to examine the research hypotheses.…”
Section: Qms Implementation and Qas Choice Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigating the factors of the internal business environment that have an impact on farmers' certification-related decisions also identified some market and public policy factors (Karipidis et al 2009;Asfaw et al 2010a, b;Masakure et al 2011;Muriithi et al 2011;Kersting and Wollni 2012;Karipidis and Tselempis 2014;Soltani et al 2014;Veldstra et al 2014). We select thirteen factors of the external business environment identified in these studies and we also add three factors that we identified in some in-depth interviews with producers as crucial in order to examine the research hypotheses.…”
Section: Qms Implementation and Qas Choice Modelsmentioning
confidence: 99%
“…Since the quality of the finished food depends substantially on the quality of the primary agricultural products, some studies have dealt with the adoption and implementation of QMS decisions in agriculture and each of them identified a number of determinants of such decisions (Karipidis et al 2009;Asfaw et al 2010a, b;Masakure et al 2011;Muriithi et al 2011;Kersting and Wollni 2012;Karipidis and Tselempis 2014;Soltani et al 2014;Veldstra et al 2014). These studies analyse the adoption/nonadoption and implementation/non-implementation decisions focusing mostly on factors of the internal business environment, adding also, in some cases, one or more factors from the market and/or policy.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural extension services have the task to translate knowledge generated at research institutes to the practice of farmers. Accordingly, smallholder farmers with access to extension services have been found to be more likely to adopt new technology and invest in new market trends, such as certification (Asfaw et al, 2010;Muriithi et al, 2011). However, public extension services in developing countries only reach a minority of smallholder farmers and are often not tailored to their needs, strategies and resource constraints .…”
Section: Linking Smallholder Farmers To High Quality Food Chainsmentioning
confidence: 99%
“…Agricultural extension services have the task to translate knowledge generated at research institutes to the practice of farmers. Accordingly, smallholder farmers with access to extension services have been found to be more likely to adopt new technology and invest in new market trends, such as certification (Asfaw et al, 2010;Muriithi et al, 2011). However, public extension services in developing countries only reach a minority of smallholder farmers and are often not tailored to their needs, strategies and resource constraints (Poulton et al, 2010).…”
Section: Institutional Constraints To Quality Improvementmentioning
confidence: 99%
“…Jaffee and Masakure, 2005;Key and Runsten, 1999). In a study on fresh vegetable producers in Kenya, Muriithi et al (2011) found that the lack of capital to cover the high costs of certification with GlobalGAP and the high costs of the recommended inputs acted as a major constraint for compliance with customers' demands. This confirms earlier findings that especially for 'risky' products, such as perishable fresh fruit and vegetables, smallholders face great difficulties in making the needed investments by themselves to link up with formal markets (e.g.…”
Section: Institutional Constraints To Quality Improvementmentioning
confidence: 99%